Active Learning Strategies Implementation in Arabic Teaching at Senior High School - Asmawati Asmawati; Asy’ari Asy’ari; Malkan Malkan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2020)
The aim of this study is to find out the implementation of active learning strategy in Arabic teaching at a senior high school in Palu city. This study used a qualitative research method. The data was collected through observation, interviews, and document analysis. The data, then, was anallysed using grounded theory approach. The results of the study illustrates that iImplementation of active learning strategies in Arabic teaching is intended as a means to deliver students to achieve Arabic learning competencies, namely: al-Istima 'competence, al-Kalaam competence, al- Qira'ah, the competence of al-Kitaabah. with the implementation of learning as follows: first, the Planning stage which contains the stages of learning planning that becomes a guide for achieving learning outcomes. Second, the Implementation stage. The teaching emphasis on the learning process which includes activities and creativity of students in gaining knowledge, skills, values, and attitudes during Arabic learning. During evaluation phase, the teacher actively measure students’ behavior changes that is used as a benchmark for planning and learning development which is aimed at assessing cognitive, affective, psychomotor aspects. The implications of the study are expected for teachers to know and apply active learning to maximize the potential and improve students’ learning outcomes.